Cigarette prices, cigarette expenditure and smoking-induced deprivation: findings from the International Tobacco Control Mexico survey. Issue 4 (25th August 2012) - Siahpush, Mohammad; Thrasher, James F; Yong, Hua H; Cummings, K Michael; Fong, Geoffrey T; de Miera, Belén Saenz; Borland, Ron
Abstract : Aim: Mexico implemented annual tax increases between 2009 and 2011. We examined among current smokers the association of price paid per cigarette and daily cigarette expenditure with smoking-induced deprivation (SID) and whether the association of price or expenditure with SID varies by income. Methods: We used data (n=2410) from three waves of the International Tobacco Control Mexico survey (ie, 2008, 2010, 2011) and employed logistic regression to estimate the association of price paid per cigarette and daily cigarette expenditure with the probability of SID ('In the last 6 months, have you spent money on cigarettes that you knew would be better spent on household essentials like food?'). Results: Price paid per cigarette increased from Mex1.24 in 2008, to Mex1.36 in 2010, to Mex1.64 in 2011. Daily cigarette expenditure increased from Mex6.9, to Mex7.6 and to Mex8.4 in the 3 years. There was no evidence of an association between price and SID. However, higher expenditure was associated with a higher probability of SID. There was no evidence that the association of price or expenditure with SID varied by income. Conclusion: Tax increases in Mexico have resulted in smokers paying more and spending more for their cigarettes. Those with higher cigarette expenditure experience more SID, with no evidence that poorer smokers are more affected.